Dança circular: inventando afetos e construindo mundos - Trindade, Tatiana Siqueira (2017)
This dissertation had the objective of comprehending the meanings of the circular dances and the affection produced by its practice. Therefore, we elaborated 2 texts: “Circular Dance and Politics: inventing worlds” and “Circular Dance: new possibilities at the university”. This text proposes a reflection about possible intertwining of the practice of dances with the politics in the interface with certain cosmovision. Through Critical Social Psychology we discuss the relation between dancing and science’s paradigms, proposed by Pedrinho Guareschi. Specifically, under Hannah Arendt's notion of politics, circular dances were focused as political potency. It is concluded that the experiences of circular dances moves possibilities of worldviews, inventing ways of experiencing politics, dances and the world, since the politics as proposed by Arendt is produced jointly, in plurality. The second text, of qualitative approach, has the objective of perceiving how the experience of a discipline that proposes the practice of circular dances affects the person at the university context. The Critical Social Psychology and the Theory of Social Representations were used, in the search of specifically understanding the ways that the practice at the discipline opens new possibilities to the academics. Through the student’s narratives in their class diaries and field diaries, we’ve concluded that the experiences of the discipline move social representations and enables sensitive experiences, both inside and outside the university, as well being in the world. Therefore, circular dance, in this research, enhances the critical reflection of constructions of spaces that can invent affection and develop other possibilities being in the world.